Onset of Microscopic Polyangiitis in Binephrectomied Patient on Chronic Hemodialysis—Case Report - Jankovic, Aleksandar; Maslarevic-Radovic, Vesna; Djuric, Petar; Tosic-Dragovic, Jelena; Bulatovic, Ana; Simovic, Nikola; Mitrovic, Milos; Stankovic-Popovic, Verica; Dopudja-Pantic, Vesna; Arandjelovic, Snezana; Dimkovic, Nada (Frontiers in Immunology, 2017)
Introduction: Microscopic polyangitis (MPA) is one of the causes of the pulmonary-renal syndrome associated with elevated nonspecific markers of inflammation and ANCA-positivity in 50-75%. De novo occurrence of the disease in patients on chronic hemodialysis has not been described. Case presentation: We presented patient who developed MPO-ANCA-associated MPA with lung and musculoskeletal involvement after four years on regular hemodialysis (HD) due to bilateral nephrectomy. After excluding the other causes of MPO-ANCA positivity, diagnosis was confirmed even without renal biopsy. Patient received standard immunosuppression therapy and he is still in remission after 27 months. Conclusion: The onset of immune-mediated disease could be observed even after introduction of renal replacement therapy (RRT) which may be a diagnostic problem. Early recognition and traditional immunosuppressive regiment may provide successful outcome.